1994
DOI: 10.1007/bf00034442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying levels of Gamborg's B5 salts and temperature on the accumulation of starch and hyoscyamine in batch cultures of transformed roots of Datura stramonium

Abstract: The partitioning of carbon between reserve polysaccharide and alkaloid secondary products was investigated in batch cultures of transformed roots of Datura stramonium grown in media in which the carbon substrate concentration was held constant and the level of mineral nutrients was varied. The growth and accumulation of starch and hyoscyamine was examined in roots grown at temperatures of 20°C, 25°C or 30°C in media containing 5% sucrose and levels of mineral nutrients varying from ¼ to twice the standard leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…From these results, it can be concluded that hyoscyamine yields increased for the duration of the experiment (Figure 1). Robins et al (1990) and Hilton and Rhodes (1994) had maximal yields after 4 weeks of cultures. These differences can be explained by the greater volume of culture medium, the small inoculum (2 root tips/flask) and by the sucrose concentration (2%) used.…”
Section: Influence Of Culture Agementioning
confidence: 95%
“…From these results, it can be concluded that hyoscyamine yields increased for the duration of the experiment (Figure 1). Robins et al (1990) and Hilton and Rhodes (1994) had maximal yields after 4 weeks of cultures. These differences can be explained by the greater volume of culture medium, the small inoculum (2 root tips/flask) and by the sucrose concentration (2%) used.…”
Section: Influence Of Culture Agementioning
confidence: 95%
“…Variables examined for their influence on growth and secondary Bonhomme et al, 2000 A. belladonna Atropine and hysocyamine Jung and Tepfer, 1987 Cinchona ledgeriana Quinine, quinidine, and cinchonidine Hamill et al, 1989 Datura innoxia Hysocyamine and scopolamine Shimomura et al, 1991a D. quercifolia Scopolamine and hysocyamine Dupraz et al, 1994 D. candida Scopolamine and hysocyamine Christen et al, 1991 Valpotriates Granicher et al, 1992 metabolite production from hairy roots include different basal media , sucrose level (Uozumi et al, 1993), exogenous supply of growth hormone (Bais et al, 2001), nature of the nitrogen source and their relative amounts (Norton and Towers, 1986), and phosphate concentration (Taya et al, 1994). Physical factors including light (Hirata et al, 1991;Yu et al, 2005), temperature (Hilton and Rhodes, 1994;Yu et al, 2005), presence of chemicals inducing physical stress (Sim et al, 1994), and magnetic field induction (Kato et al, 1989) have also been reported to affect secondary metabolite production from hairy roots. Betacyanin release from hairy roots of Beta vulgaris was achieved by oxygen starvation .…”
Section: Secondary Metabolite Production From Hairy Rootsmentioning
confidence: 98%